A framework for addressing urban heat challenges and associated adaptive behavior by the public and the issue of willingness to pay for heat resilient infrastructure in Chongqing, China. (December 2021) - He, Bao-Jie; Zhao, Dongxue; Xiong, Ke; Qi, Jinda; Ulpiani, Giulia; Pignatta, Gloria; Prasad, Deo; Jones, Phillip
Highlights: This paper develops a framework for urban heat prevention, mitigation and adaptation. Air-conditioning systems are the dominant cooling facility in both work and living environments. Urban planning and design for heat resilient cities is the most urgent intervention. 50% of the respondents preferred collaborative payment among government, developers, and owners for heat resilient infrastructure. Heat-related responses and actions towards urban heat challenges were dependent demographic factors and their exposure, habit formation and behavior change, social acceptance. Abstract: This study investigates public participation in heat impact reduction by analysing adaptive behaviours, familiarity with urban heat island (UHI) and cooling strategies, the perceived urgency of heat impact actions and citizen's willingness to pay through a questionnaire survey in Chongqing, China. The results indicate that air-conditioning systems are the dominant cooling facility in both work and living environments. Respondents had a moderately familiar understanding of several cooling strategies such as urban vegetation, shading devices, water-based artificial facilities, urban design for shading and ventilation and water bodies. Familiarity with innovative materials and techniques for pavements, roofs and façades was less than moderate. Urban planning and design for heat resilient cities was thought to be the most urgent intervention, followed by the establishment of temporary cooling facilities. Most respondents indicated that cost-sharing mechanisms for urban heat prevention and control systems should at least include the government, whilst 50% of the respondents preferred collaborative payment among government, developers, and owners. Only 41.6% of the interviewees expressed their willingness to pay, with a share varying between <20 and >80 RMB. A conservative estimate indicated that there could be an average payment of 45.95 RMB and 19.10 RMB among the 234 respondents who were willing to pay and all 562 respondents regardless of willingness, respectively. Respondents' heat-related responses and actions towards urban heat challenges were dependent on a wide range of factors like gender, age, education, economic status, health, exposure, habit formation and behavior change, social acceptance, etc. Moreover, such factors could interact with each other affecting public behavior with different weights. Overall, this study increases our understanding of people's perceptions and proactiveness in reducing urban heat and provides guidance for decision-makers towards a novel user-aware approach to the implementation of urban heat prevention, adaptation, and mitigation strategies.